Presence or absence of microbiome modulates the response of mice organism to administered drug nabumetone - Jourová, Lenka; Lišková, Barbora; Lněničková, Kateřina; Zemanová, Nina; Anzenbacher, Pavel; Hermanová, Petra; Hudcovic, Tomáš; Kozáková, Hana; Anzenbacherová, Eva (Physiological research, 2020)
The gut microbiota provides a wide range of beneficial functions for the host, and has an immense effect on the host's health status. The presence of microbiome in the gut may often influence the effect of an orally administered drug. Molecular mechanisms of this process are however mostly unclear. We investigated how the effect of a nonsteroidal drug nabumetone on expression of drug metabolizing enzymes (DMEs) in mice intestine and liver is changed by the presence of microbiota, here, using the germ free (GF) and specific pathogen free (SPF) BALB/c mice. First, we have found in a preliminary experiment that in the GF mice there is a tendency to increase bioavailability of the active form of nabumetone, which we have found now to be possibly influenced by differences in expression of DMEs in the GF and SPF mice. Indeed, we have observed that the expression of the most of selected cytochromes P450 (CYPs) was significantly changed in the small intestine of GF mice compared to the SPF ones. Moreover, orally administered nabumetone itself altered the expression of some CYPs and above all, in different ways in the GF and SPF mice. In the GF mice, the expression of the DMEs (CYP1A) responsible for the formation of active form of the drug are significantly increased in the small intestine and liver after nabumetone application. These results highlight the importance of gut microbiome in processes involved in drug metabolism in the both gastrointestinal tract and in the liver with possible clinical relevance.
Keywords: tenké střevo; střevní mikroflóra; nabumeton; Transcription Factors; metabolická aktivace; Activation, Metabolic; systém (enzymů) cytochromů P-450; Mice, Inbred BALB C; Anti-Inflammatory Agents, Non-Steroidal; Bacteria; transkripční faktory; myši inbrední BALB C; zvířata; Administration, Oral; Gastrointestinal Microbiome; antiflogistika nesteroidní; cytochrom P-450 CYP1A1; Nabumetone; dysbióza; Cytochrome P-450 CYP1A1; Intestine, Small; aplikace orální; Liver; Animals; játra; Cytochrome P-450 Enzyme System; Dysbiosis